If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -1) = x + 1 Reorder the terms: 2(-1 + 2x) = x + 1 (-1 * 2 + 2x * 2) = x + 1 (-2 + 4x) = x + 1 Reorder the terms: -2 + 4x = 1 + x Solving -2 + 4x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 4x + -1x = 1 + x + -1x Combine like terms: 4x + -1x = 3x -2 + 3x = 1 + x + -1x Combine like terms: x + -1x = 0 -2 + 3x = 1 + 0 -2 + 3x = 1 Add '2' to each side of the equation. -2 + 2 + 3x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 1 + 2 3x = 1 + 2 Combine like terms: 1 + 2 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| e^2-7x=1324 | | 8x^2+8+8x=13 | | log(2v+7)=log(3v-6) | | -x=8-5x^2 | | 192-16p=0 | | -4.5+2y=-6 | | 2x^2+6x+5=16x | | log(2x+9)=log(9-4x) | | 2x+4-10x^2=8x | | 9-y(9x)=1 | | 20x+15x-20(x-1)+15(x-1)=245 | | 2*(sin(x))= | | 4x-(2x+6)=90 | | a^2+100=38 | | 8(1y+6)+y=31 | | -5-u=4u | | 4x^2-3=77 | | 3ab-a-2b-2=0 | | 3ab-a=2b+2 | | f(x+y)-f(x-y)=5xy+2y | | 8(-4.5)+7.5=31 | | 3+p=7 | | 4l-2.6=13.4 | | 24uw^5y^2+28u^4w^8= | | -3+9m=-10m | | 3x(x-7)=3+5 | | 9x(9-y)-1=0 | | 2(x-5)-12=2x-22 | | 4a-6b=10 | | 2(x-3)=3x-9 | | c^2=5 | | (3x+1)(x+9)=0 |